Effect of Resistance Training With Total and Partial Blood Flow Restriction on Biomarkers of Oxidative Stress and Apoptosis in Untrained Men - de Lima, Fabio Rocha; Marin, Douglas Popp; Ferreira, Letícia Torres; Sousa Filho, Celso Pereira Batista; Astorino, Todd Anthony; Prestes, Jonato; Marquezi, Marcelo Luis; Otton, Rosemari (Frontiers in Physiology, 2021)
The characterization of immune and oxidative stress responses to acute and chronic exercise training is important because it may aid in the safety and dose-response prescription of resistance training in many populations. Purpose: The present study compared changes in acute oxidative stress and markers of apoptosis in immune cells before and after 8 weeks of low-load resistance training (RT) with total or partial blood flow restriction (BFR) versus high-load traditional RT. Methods: Twenty-seven untrained men were randomly divided into three groups: traditional RT (75% 1-RM), RT with partial (20% 1-RM), and total BFR (20% 1-RM). Over an 8 week period, participants performed 6 sets of arm curls until failure with 90 seconds of recovery, 3 d/week. Blood samples were obtained before and after the first and last training sessions. Results: Data indicated that all training groups showed similar increases in muscular strength (p<0.001), reduction in mitochondrial membrane potential after exercise in neutrophils (p<0.001), and an increase in caspase-3 activity after exercise (p<0.001). Traditional RT and total BFR showed increased plasma lipid peroxidation (p<0.001) and protein carbonyls (p<0.001) and lower levels of reduced glutathione (p<0.001) after exercise. No change was observed in oxidative stress biomarkers in response to partial BFR (p>0.05). Conclusion: Data show that RT with partial BFR can increase muscular strength yet does not augment biomarkers of oxidative stress in untrained men. In addition, RT with total BFR promoted similar responses of oxidative stress and markers of immune cells apoptosis versus traditional RT.